Blue Aggregation‐Induced Emission Luminogens: High External Quantum Efficiencies Up to 3.99% in LED Device, and Restriction of the Conjugation Length through Rational Molecular Design. (13th October 2014) - Huang, Jing; Sun, Ning; Yang, Jie; Tang, Runli; Li, Qianqian; Ma, Dongge; Li, Zhen
<x xml:space="preserve">Abstract</x> Great efforts have been devoted to seek novel approaches for constructing blue fluorescent materials, which is one of the most important prerequisites for the commercialization of OLEDs. In recent years, various outstanding luminogens with aggregation‐induced emission characteristic exhibit promising applications as emitters, but blue AIE fluorophores with excellent EL performance are still very scarce. Here, five hole‐dominated blue AIE molecules are demonstrated by adopting construction approaches of changing linkage modes and increasing intramolecular torsion together, with the aim to restrict conjugation lengths without sacrificing good EL data. Device results show that the novel synthesized materials could be applied as bifunctional materials, namely blue light‐emitting and hole‐transporting materials, with comparable EL efficiencies, and the ηC, max and ηext, max are up to 8.03 cd A−1 and 3.99% respectively, which is among the best EL performance for blue AIE luminogens.